Pengaruh Kualitas Layanan Mobile Banking Terhadap Kepuasan Nasabah Bank BCA - Palupi Permata Rahmi; Nur Aryanti, Asti; Abdul Aziz, Dadan (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to determine how much influence service quality has on customer satisfaction at Bank BCA Bandung City. The sample used is 50 customers. This study used validity test, correlation coefficient test, coefficient determination test, multiple linear regression analysis and hypothesis testing which was prepared using SPSS. Based on the research results, it can be seen that the contribution of service quality to customer satisfaction is 67.80%, the remaining 32.20%, influenced by other factors not examined. In addition, from the research results it is known that the Tangible (X1) and Responsiveness (X3) variables have a partial effect on Customer Satisfaction (Y). While partially the Empathy (X2), Reliability (X4), and Assurance (X5) variables have no effect on Customer Satisfaction (Y). Simultaneously, Tangible Variables (X1), Empathy (X2), Responsiveness (X3), Reliability (X4), and Assurance (X5) have an effect on Customer Satisfaction (Y).